Testing the Effectiveness of Soursop Leaf Infusion (Annona Muricata) as a Natural Larvicide against Aedes Aegypti Mosquito Larvae: Uji Efektivitas Infusa Daun Sirsak (Annona Muricata) sebagai Larvasida Alami terhadap Jentik Nyamuk Aedes Aegypti - Selly Tria Amanda; Marmi; Sunaryo (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2026)
Aedes aegypti mosquitoes are the primary vectors responsible for dengue hemorrhagic fever (DHF), which remains a significant public health problem. The continuous use of chemical larvicides has the potential to cause resistance and negative environmental impacts; therefore, alternative natural larvicides are needed. One plant with potential as a natural larvicide is soursop leaves (Annona muricata). This study aimed to determine the effectiveness of different temperatures in the preparation of soursop leaf infusion (Annona muricata) on the mortality of Aedes aegypti larvae. The research method employed was an experimental design with soursop leaf infusion treatments at temperatures of 60°C, 70°C, and 80°C, with distilled water used as the control. The results showed that the 60°C treatment produced the highest average larval mortality of 10.33 larvae, followed by 5.33 larvae at 80°C and 3 larvae at 70°C, while no larval mortality was observed in the control group. Based on these findings, soursop leaf infusion prepared at 60°C was the most effective treatment in increasing the mortality of Aedes aegypti larvae and has the potential to be developed as an environmentally friendly natural larvicide.